The reflections of social media platforms on intellectual security: An applied study of students of King Faisal University - Saleh, Shoeb Gamal; Helali, Mamdouh Mosaad; Ibrahim, Khaled Ahmed Abdel-Al (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to examine how social media networks influence intellectual perceptions among students at King Faisal University. Employing a descriptive research design, the investigation focused specifically on the impact of social media platforms on security-related thought, particularly within social and political contexts. The findings indicate that WhatsApp, Snapchat, and Instagram are the most frequently used networks among these students. Moreover, the results reveal that social media’s influence on security thought is strongly associated with social and infrastructural effects, moderately linked to economic effects, and demonstrates a significant correlation with considerable economic impact as measured by the questionnaire. Although no statistically significant differences were found in responses based on gender, academic specialization, or level, significant variations emerged in the definition of specialization and its relationship with the effects of social media on intellectual perceptions. Based on these results, the study recommends establishing an educational institution within the university dedicated to social communication. This institution would offer guidance programs aimed at regulating the design and use of social media in academic settings while also emphasizing the importance of enacting and enforcing legislation to prevent the dissemination of extremist or harmful content.